การศึกษาการดำเนินงานวิชาการของโรงเรียนในกลุ่มนวมินทราชินูทิศ สังกัดกรมสามัญศึกษา - เรณู ครุธไทย (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The purpose of this research was to study the operation of academic tasks and problems of schools in Nawamintarachinutis group under the Department of General Education. The population of the study was school administrators, assistant administrators and department heads. The research instruments were structured interview form and documentary analysis form. Data were analyzed by using frequency and percentage. Research findings were as follows: 1.) Regarding academic plan, most schools had regulation and guidelines for operation academic tasks and school administrators informed in meeting. Each section had prepared academic plan together and presented to the school administrators. 2.) In organizing academic work, staff were assigned according to their knowledge, abilities and experiences. Learning group were arranged in required subjects and elective subjects and schools allowed students to choose. The timetable was covered subjects required in the curriculum. Teachers were assigned to teach the subjects according to their majors. The educational innovation and technology were utilized and produced by teachers. 3.) Concerning the instructional management, teachers prepared lesson plans according to the curriculum and subject contents. They produced and utilized instructional media. Schools followed up the utilization of media by observing teachers instruction. 4.) In developing and supporting the academic tasks, schools organized in-service training by providing conference, seminars and workshops on teaching methodology before the schools started. The schools provided the remedial teaching for students who were weak in any courses or did not reach the school standard criteria for one period per week. Moreover, the schools provided both academic activities and extra curriculum activities for the students according to the school readiness and the policies of the schools and upper division. The schools had the policy to encourage the teachers attending academic conference, seminars and workshops including the study visit. Besides, the schools had created the academic atmosphere by providing the academic centers for each department. 5.) In the measurement evaluation, registration and student records, the schools had the operation schedule and the action guides for the teachers. Each teacher had to construct his/her own measurement tools appropriate to the learning objectives of each course. The registra and the student recorders had to record about the student histories; accredited and recorded the student grades. 6.) Regarding assessment and evaluation of the academic tasks organization, most schools regularly set the conferences, seminars to summarize the results of academic tasks and to evaluate the works of each section. In the aspect of the academic management problems, it was found that the budget was not sufficient, all departments could not provide various courses to serve the student needs. The teachers made very few teaching aids. The students not only paid attention to the remedial teaching for improving their knowledge but also followed up their regrade for the courses which they failed. Some teachers did not improved or developed measurement tools. There was a shortage of teachers. Moreover, they had too many extra jobs assigned by the schools so that they could not produce academic works effectively.